Experimental Characteristics of Mechanical Continuously Variable Transmission with Internal Force Functions - A. V. Yurkevich; A. V. Tereshin; V. A. Soldatkin (Наука и техника)
The paper proposes a new type of a mechanical continuously variable transmission with internal force functions  to upgrade the energy efficiency of a vehicle equipped with a conventional engine. The prototype of the transmission is a well-known V. F. Maltsev concurrent pulse variator in which freewheel mechanism driven members are supplemented with elastic torsions shafts. It is shown that the variator turns into a continuous transformer – a mechanical continuously variable transmission with internal force functions. There is an internal automaticity and continuity in the entire range of gear ratio changes. The configuration engineering solution is implemented in the engineering prototype. The aim of the research is experimental study of the properties and characteristics of such a mechanical continuously variable transmission. The kinematic configuration and the main structural dimensions of the engineering prototype are given. Special testing facility and measuring-and-recording equipment have been developed. A set of parameters to be recorded has been specified. The accuracy of their measurement is statistically estimated. The results of the experiments are presented in terms of output and input torque dependencies on the speed of the driven shaft. It is shown that the transmission characteristics in their dimensionless form (transformer ratio and efficiency) in the function of internal gear ratio are universal. The possibility of obtaining an infinite kinematic and significant power transmission ranges by independently changing the internal link oscillation range (level of the force function) and the rotation frequency of the drive shaft has been experimentally shown. The transmission  has high transforming and energy properties, which are higher than those of hydrodynamic gears.